Structural basis of mutants of PET‐degrading enzyme from Saccharomonospora viridis AHK190 with high activity and thermal stability. Issue 5 (24th December 2020) - Emori, Miho; Numoto, Nobutaka; Senga, Akane; Bekker, Gert‐Jan; Kamiya, Narutoshi; Kobayashi, Yuma; Ito, Nobutoshi; Kawai, Fusako; Oda, Masayuki
Abstract: The cutinase‐like enzyme from the thermophile Saccharomonospora viridis AHK190, Cut190, is a good candidate to depolymerize polyethylene terephthalate (PET) efficiently. We previously developed a mutant of Cut190 (S226P/R228S), which we designated as Cut190* that has both increased activity and stability and solved its crystal structure. Recently, we showed that mutation of D250C/E296C on one of the Ca 2+ ‐binding sites resulted in a higher thermal stability while retaining its polyesterase activity. In this study, we solved the crystal structures of Cut190* mutants, Q138A/D250C‐E296C/Q123H/N202H, designated as Cut190*SS, and its inactive S176A mutant, Cut190*SS_S176A, at high resolution. The overall structures were similar to those of Cut190* and Cut190*S176A reported previously. As expected, Cys250 and Cys296 were closely located to form a disulfide bond, which would assuredly contribute to increase the stability. Isothermal titration calorimetry experiments and 3D Reference Interaction Site Model calculations showed that the metal‐binding properties of the Cut190*SS series were different from those of the Cut190* series. However, our results show that binding of Ca 2+ to the weak binding site, site 1, would be retained, enabling Cut190*SS to keep its ability to use Ca 2+ to accelerate the conformational change from the closed (inactive) to the open (active) form. While increasing the thermal stability, Cut190*SS could still express its enzymatic function. Even after incubation at 70°C, which corresponds to the glass transition temperature of PET, the enzyme retained its activity well, implying a high applicability for industrial PET depolymerization using Cut190*SS.